2019
DOI: 10.1007/s10096-019-03630-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-world efficacy of bezlotoxumab for prevention of recurrent Clostridium difficile infection: a retrospective study of 46 patients in five university hospitals in Finland

Abstract: Reports on real-world experience on efficacy of bezlotoxumab (BEZ) has been lacking thus far. We retrospectively studied the efficacy and safety of BEZ in preventing the recurrence of Clostridium difficile infection (CDI) in five university hospitals in Finland. Seventy-three percent of our 46 patients remained free of recurrence in the following 3 months and the performance remained as 71% effective also among immunocompromised patients. In severe CDI, BEZ prevented recurrence in 63% of cases. From our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
6
20
1
Order By: Relevance
“…These data indicated that patients with transient deficiency in IgA might be more susceptible for infection. Well in line with this observation Bezlotoxumab, a monoclonal antibodies directed against TcdB, prevented recurrence of CDI, highlighting the value of antibody-mediated toxin neutralization ( 119 , 120 ).…”
Section: Microbiological and Immunological Susceptibility To supporting
confidence: 61%
“…These data indicated that patients with transient deficiency in IgA might be more susceptible for infection. Well in line with this observation Bezlotoxumab, a monoclonal antibodies directed against TcdB, prevented recurrence of CDI, highlighting the value of antibody-mediated toxin neutralization ( 119 , 120 ).…”
Section: Microbiological and Immunological Susceptibility To supporting
confidence: 61%
“…A higher risk of rCDI was observed in patients with ≥ 2 previous recurrences before receiving bezlotoxumab (hazard ratio 2.77, 95% CI 1.14–6.76, p = 0.025) [ 68 ]. Another multicentre, retrospective case series was conducted in five university hospitals in Finland [ 69 ]. The study included 46 CDI patients who received a standard dose of bezlotoxumab.…”
Section: Methodsmentioning
confidence: 99%
“…This could have resulted in a greater proportion of diarrhoea recurrences classified as rCDI The study observed successful prevention of rCDI with bezlotoxumab comparable to clinical trial results. Multiple prior rCDI were associated with a higher risk of subsequent rCDI Oksi J et al 2019 [ 69 ] Retrospective study April 2017–December 2017 Finland 46 CDI patients treated with bezlotoxumab. Mean age: 66 years (range 15–97) Mean number of CDI previous episodes: 2.74 (range 1–7) 28/46 (61%) were immunocompromised and 36/46 (78%) had three or more risk factors for rCDI Vancomycin in 37/46 patients, metronidazole in 9/46, fidaxomicin in 7/46, and tigecycline in 2/46 rCDI in the 3 months after bezlotoxumab infusion Overall, 73% of the patients remained free of rCDI in the following 3 months after bezlotoxumab infusion, 71% of the immunocompromised patients remained free of rCDI during the follow-up, 63% of the severe CDI cases remained free of rCDI during the follow-up Two possible infusion-related adverse reactions: one patient experienced startling sensations after the infusion; one patient presented with fever in the following day after the infusion Detection of CD toxin gene by polymerase chain reaction was the only method used to detect CDI Bezlotoxumab infusion as an adjunctive treatment to anti-CD antimicrobial treatment prevented rCDI in a major proportion of enrolled patients, including immunocompromised individuals CD Clostridioides difficile , CDI Clostridioides difficile infection, rCDI recurrent Clostridioides difficile infection, RCTs randomized controlled trials …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations